Islamic Education Based on Arabic Pegon Letters in Madrasah Diniyah Al Barokah Watuagung Tambak Banyumas - Mohammad 'Ulyan; Nurti Budiyanti; Shepta Adi Nugraha (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This article aimed to analyze the Islamic education based on Pegon Arabic letters in Madrasah Diniyah Al-Barokah Watuagung. This research was qualitative research. Observation, interview and documentation were collecting data of research. The participants consist of 30 students and 5 teachers as research sample. The results showed that Madrasah Diniyah Al-Barokah used the Arabic letters Pegon in learning. This Madrasah still exists amid the vortex of globalization to preserve the legacy of civilization for superior Islamic education. The curriculum was taught in the form of Fikih, Morals, Aqidah, Tajwed, Al-Quran, Nahwu and Sharaf. Islamic education was taught by teachers who are graduates of various Pesantren at Java, hence they were scientifically and experienced. Keywords: Islamic Education, Arabic Pegon, Pegon Letter